Scooping Review: The Effectiveness of Physical Training Based on Child Health Models for Obese Adolescents - Rismanudin Rismanudin; Fony Fony; Wahyuni Wahyuni; Umriani Syamsuddin (GLOBAL HEALTH SCIENCE GROUP, 2025)
Adolescent obesity is a global public health concern that affects both physical health and psychosocial well-being. Integrative interventions that combine physical training with psychosocial support, such as the Child Healthcare Model, are increasingly being used to address this issue holistically. This study aims to explore the effectiveness of physical training based on the Child Healthcare Model on weight loss and body image among obese adolescents through a scoping review guided by the PRISMA framework. This study aims to assess the effectiveness of physical exercise based on the Child Healthcare Model in reducing weight and improving body image in obese adolescents. It is hoped that the results of this study will provide a deeper nunderstanding of the role of structured physical exercise in supporting obese adolescents to achiev their ideal weight and form a more positive body image. A comprehensive literature search was conducted using PubMed, Scopus, ScienceDirect, and Google Scholar databases for relevant studies published between 2019 and 2024. The search focused on studies involving adolescents aged 12–18 years with obesity who underwent physical training programs integrated with the Child Healthcare Model. Study selection followed the PRISMA-ScR flow diagram, and data were extracted and synthesized narratively. Out of 187 initial articles, 23 met the inclusion criteria. Most studies reported that physical training combined with the Child Healthcare Model—through nutritional education, psychological support, and family involvement—resulted in average weight loss of 3–5% over 12 weeks and significantly improved body image as measured by validated scales. Family and professional involvement were key factors in enhancing participant motivation and outcomes. Physical training based on the Child Healthcare Model is effective in reducing body weight and improving body image among adolescents with obesity. These findings support the implementation of holistic, family-centered interventions in adolescent obesity programs.